Strategi Guru Dalam Pembelajaran PAI Pada Anak Berkebutuhan Khusus - Difa’ul Husna; Bayu Agung Maulana; Muhammad Alfian Darmawan; M Nouval SR (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
Every human being cannot choose whether he will be born in a perfect condition or not. Whether you are born perfect or not is God's decree. Every parent must be aware of this, so that they do not consider that their child being born as an individual with special needs is a disgrace and a disaster. They deserve education and teaching, because they too have been given the potential by God to understand their needs for survival. Regarding how to educate them is an interesting issue to research, so this research will discuss qualitatively related to teacher strategies in teaching PAI to children with special needs at SLB Yaketunis, Yogyakarta. The results of this research concluded that the teacher's strategy in learning Islamic Religious Education for children with special needs at Yaketunis SLB begins with consideration of several aspects, namely: 1) service to students which focuses on teacher behavior patterns in educational interactions at school; in aspects, and 2) aspects of implementing learning using demonstration and familiarization methods, especially in religious practice materials..